Une expérience malheureuse de la mer du Nord : des Vénitiens aux Lofoten (vers 1432) - Laget, Frédérique (Presses universitaires de Rennes, 2019)
In November 1431, a Venetian ship travelling from the Mediterranean to Flanders veered off course and got lost in the North Sea, where it sank. The survivors drifted for weeks and eventually reached Røst, an island lying south of the Lofoten islands, without knowing where they were. They were then taken in for three months by the islanders. Three members of this unfortunate crew wrote down their adventures after their return to Venice: Pietro Querini, the master of the ship, Cristoforo Fioravante, the second officer, and Nicolò de Michiel, the board writer. According to their texts, during their stay they discovered a harsh environment that contrasted with the gentle people of this distant North. The Venetians noticed the marvels of nature, but what struck them most was the great honesty and moral pureness of the population on Røst; they considered these fishermen to be pious, simple, and friendly, in spite of their living in a very remote area at the ends of the earth. Meeting the inhabitants of Røst somehow meant meeting complete otherness. To the marooned sailors, the island looked like a kind of Eden and the experience turned their misfortune into an ordeal of faith. It changed them physically as well as morally.